Izboljšanje dinamičnih značilnosti rotorskega sistema z razvojnim algoritmom - Saruhan, Hamit (Strojniški vestnik, 2007)
In this paper the optimum design for improving the dynamic characteristics of a flexible, overhung rotor system is studied. The design of a flexible rotor system is a complicated process due to the large number of geometrical parameters of hydrodynamic bearings, which play an important role in the prediction of the dynamic behavior of the rotor system. There are a number of design requirements added to the rotor-system configuration that improve the dynamic characteristics within the rotorćs speed range. To improve the dynamiccharacteristics of the rotor system, a genetic algorithm was employed and the modeling of the components of the rotor system was made with the finite-element method. Also, the method of feasible directions was used in order to validate the efficiency and applicability of the proposed method, andit proved that the proposed method in the rotor-system design is very efficient and useful for improving the dynamic characteristics of the rotor system.
Keywords: rotorji; dinamične lastnosti; optimiranje; genetski algoritmi; metoda končnih elementov; finite element method